Perlindungan Hukum terhadap Notaris Penerima Protokol: Bentuk dan Batasan - Yetniwati Yetniwati; Taufik Yahya; Diana Amir (Fakultas Hukum Universitas Jambi, 2021)
A notary is a public official authorized to draw up and keep authentic deeds and other documents permitted by laws and regulations. Whenever a notary dies, or reaches retirement age, changes his/her domicile or profession, he/she shall submit his/her retired notary protocol to another notary appointed by the Regional Supervisory Council. The submission of notary protocol is regulated in Article 65 of the Law on Notary Positions, yet without legal protection. In some cases, court decisions are found to have imposed sanctions upon a notary who received the protocol despite the mistake of the notary protocol giver. This article encourages that the notary who receives the protocol be provided with legal protection, because he/she is only the party who receives the protocol made by another notary. The imposition of responsibility upon the notary protocol recipient regarding the contents of the deed he/she keeps will only lead to injustice and legal uncertainty. Since no regulation has been provided concerning to such matter, it is necessary to afford legal protection which comprises: the responsibility of the heirs of the notary (giver); the limitation of the responsibility of the protocol recipient; the limitation of protocol retention time; and the necessity of storing notary protocols in the form of microfilm. Nevertheless, the notary protocol recipient shall also have limited protection, in the sense that he/she can be held accountable with respect to the obligation to keep the notary protocol he/she receives in proper ways. Abstrak Notaris adalah pejabat umum yang berwenang membuat dan menyimpan akta dalam bentuk akta otentik, serta dokumen lain yang diperbolehkan oleh perundang-undangan. Setiap notaris yang meninggal dunia, mencapai usia pensiun, pindah domisili, atau pindah profesi, wajib menyerahkan protokol notarisnya kepada notaris lain yang ditunjuk oleh Majelis Pengawas Daerah. Pengaturan penyerahan protokol notaris diatur dalam Pasal 65 Undang-undang Jabatan Notaris, namun tidak dengan perlindungan hukumnya. Dalam beberapa kasus dijumpai putusan pengadilan yang memberikan sanksi kepada notaris penerima protokol sekalipun berkaitan dengan kesalahan notaris pemberi protokol. Artikel ini mendorong agar notaris penerima protokol mendapatkan perlindungan hukum, sebab ia hanya sebagai pihak yang menerima protokol yang dibuat oleh notaris lainnya. Pembebanan tanggung jawab kepada notaris penerima protokol terkait isi akta yang disimpannya justru akan menyebabkan ketidakadilan dan ketidakpastian hukum. Oleh karena sejauh ini belum ada pengaturannya, maka perlu diupayakan perlindungan hukum yang meliputi: tanggung jawab ahli waris notaris (pemberi); batasan tanggung jawab penerima protokol; batasan waktu penyimpanan protokol; dan keharusan penyimpanan protokol notaris dalam bentuk mikrofilm. Meski demikian, notaris penerima protokol tentu harus pula dibatasi perlindungannya, dalam artian dapat dimintai pertanggungjawabannya, yaitu dalam hal keharusannya menyimpan protokol notaris yang diterimanya secara patut.